Method for estimating tensiomyography parameters from motion capture data - Vlahek, Dino; Stošić, Tadej; Golob, Tamara; Kalc, Miloš; Ličen, Teja; Vogrin, Matjaž; Mongus, Domen (Informatica, 2021)
Tensiomyography is a muscle performance assessment technique that measures its mechanical responses. In this study, we explore a possibility to replace traditional tensiomyography measurement system with motion capture. The proposed method allows for measurement of multiple muscle's points simultaneously, while achieving measurements during a patient's movements. The results show that approximately 5 mm error is achieved when estimating maximal muscle displacement, while time delay in muscle contraction and contraction time are assessed with upto 20 ms error. As confirmed by physicians, the introduced errors are with the acceptable margin and, thus, the obtained results are medically valid.